National Survey of Oral/Dental Conditions Related to Tobacco and Alcohol Use in Mexican Adults - Medina-Solís, Carlo Eduardo (MDPI, 2014)
Oral diseases are a major burden on individuals and health systems. The aim of this study was to determine whether consumption of tobacco and alcohol were associated with the prevalence of oral/dental problems in Mexican adults. Using data from the National Performance Evaluation Survey 2003, a cross-sectional study part of the World Health Survey, dental information from a representative sample of Mexico (n = 22,229, N = 51,155,740) was used to document self-reported oral/dental problems in the 12 months prior to the survey. Questionnaires were used to collect information related to sociodemographic, socioeconomic, and other risk factors. Three models were generated for each age group (18–30, 31–45 and 46–98 years). The prevalence of oral/dental conditions was 25.7%. Adjusting for sex, schooling, socioeconomic position, diabetes, and self-reported health, those who used tobacco (sometimes or daily) (OR = 1.15, p = 0.070; OR = 1.24, p < 0.01; and OR = 1.16, p < 0.05, for each age group respectively) or alcohol (moderate or high) (OR = 1.26, p < 0.001; OR = 1.18, p < 0.01 and OR = 1.30, p < 0.001, for each age group respectively) had a higher risk of reporting oral/dental problems. Because tobacco and alcohol use were associated with self-reported oral/dental problems in one out of four adults, it appears advisable to ascertain how direct is such link; more direct effects would lend greater weight to adopting measures to reduce consumption of tobacco and alcohol for the specific purpose of improving oral health.